Grammar Form and Function - High Intermediate: Student Book Bk. 3b - Broukal Milada (New York : Mc Graw Hill, 2005)
Contents
Unit 8: The passive voice. Causatives. And phrasal verbs
Unit 9: Gerunds and infinitives
Unit 10: Agreement and parallel structure
Unit 11: Noun clauses and reported speech
Unit 12: Adjective clauses
Unit 13: Adve?b clauses
Unit 14: Condtional sentences
Keywords: Ngôn ngữ --Anh; Grammar--form--function